Cytosolic NUAK1 Enhances ATP Production by Maintaining Proper Glycolysis and Mitochondrial Function in Cancer Cells - Escalona, Emilia; Muñoz, Marcelo; Pincheira, Roxana; Elorza, Álvaro A.; Castro, Ariel F. (Frontiers in Oncology, 2020)
NUAK1 is an AMPK-related kinase located in the cytosol and the nucleus, whose expression associates with tumor malignancy and poor patient prognosis in several cancers. Accordingly, NUAK1 was associated with metastasis because promotes cell migration and invasion in different cancer cells. In addition, NUAK1 supports cancer cell survival under metabolic stress and maintains ATP levels in hepatocarcinoma cells, suggesting a role in energy metabolism in cancer. However, it is unclear the underlying mechanism for this metabolic function and how it is linked to NUAK1 subcellular localization. We demonstrated that cytosolic NUAK1 increases ATP levels, which associates with increased mitochondrial respiration and decreased mitochondrial membrane potential, supporting that cytosolic NUAK1 is involved in mitochondrial function regulation in cancer cells. NUAK1 inhibition lead to the formation of “donut-like” structures, providing evidence of NUAK1-dependent mitochondrial morphology regulation. Additionally, our results indicate that cytosolic NUAK1 increases the glycolytic capacity of cancer cells under mitochondrial inhibition, but nuclear NUAK1 seems to be involved in the glycolytic switch. Altogether, our results suggest that cytosolic NUAK1 participates in mitochondrial ATP production and in the maintenance of proper glycolysis in cancer cells. Our current studies support a role of NUAK1 in the bioenergetic, mitochondrial homeostasis, glycolysis and metabolic capacities, suggesting different metabolic outcomes depending on its subcellular localization. The identified roles of NUAK1 in cancer metabolism provide a potential mechanism relevant for tumor progression, and for its association with poor patient prognosis in several cancers. Further studies could shed light on the molecular mechanisms involved in the identified metabolic NUAK1 functions.